Legal Protection for Traditional Medicine Knowledge of Paliasa Leaves in Traditional Community of South Sulawesi Through Intellectual Property Regime - Muhammad Tizar Adhiyatma; Kholis Roisah (LAW REFORM, 2020)
Traditional knowledge as a work which is communal property and has opposition characteristics to the legal regime of Intellectual Property rights. Thus, imposing for a regime of intellectual property used as a system to protect traditional knowledge would only cause anomalies in Indonesian society itself and the existing legal regime of Intellectual Property rights in Indonesia is not yet capable of protecting traditional knowledge, especially that associated with genetic resources. The existence of local wisdom of communities in South Sulawesi to genetic resources is to use Paliasa (Kleinhovia Hospita Linn.) leaf as a medicinal plant which are well documented in ancient texts “lontarak pabbura” and organized by Ammatoa as Kajang indigenous leaders. Therefore, it needs a protection model to protect traditional knowledge and their genetic resources associated with traditional knowledge through a sui generis system as positive protection and defensive protection models in order to provide comprehensive protection against traditional knowledge belonging to the Indonesian people.